PENGARUH KEWAJIBAN KEPEMILIKAN NPWP,PEMERIKSAAN PADAJAN DAN PENAGIHAN PAJAK TERHADAP PENERIMAAN PAJAK (Studi Kasus pada KPP Pratama Bitung) - Simanungkalit, Adelina; Poputra, Agus T.; Runtu, Treesje (Universitas Sam Ratulangi, 2015)
This research aimed to analyze the influence of ownership obligations Taxpayer Identification Number, tax audit and tax collection on tax revenue. The respondents in this research were tax officer at Tax Office Bitung. Total of sample in this research are 30 person from 79 person of tax officer on Tax Office Bitung. The sampling method in this research used nonprobability sampling through purposive sampling technique. While the data processing method was used multiple regression analysis. The result showed that the obligation of ownership Taxpayer Identification Number and tax collection did not significantly affect tax revenues, while the variable of tax audit proved to have a significant positive effect on tax revenues.